Effects of Insulin Therapy on Myocardial Lipid Content and Cardiac Geometry in Patients with Type-2 Diabetes Mellitus - Jankovic, Drazenka; Winhofer, Yvonne; Promintzer-Schifferl, Miriam; Wohlschläger-Krenn, Evelyne; Anderwald, Christian Heinz; Wolf, Peter; Scherer, Thomas; Reiter, Gert; Trattnig, Siegfried; Luger, Anton; Krebs, Michael; Krssak, Martin (PLOS ONE, 2012)
Aims/Hypothesis Recent evidence suggests a link between myocardial steatosis and diabetic cardiomyopathy. Insulin, as a lipogenic and growth-promoting hormone, might stimulate intramyocardial lipid (MYCL) deposition and hypertrophy. Therefore, the aim of the present study was to investigate the short-term effects of insulin therapy (IT) on myocardial lipid content and morphology in patients with T2DM. Methods Eighteen patients with T2DM were recruited (age 56±2 years; HbA1c: 10.5±0.4%). In 10 patients with insufficient glucose control under oral medication IT was initiated due to secondary failure of oral glucose lowering therapy (IT-group), while 8 individuals did not require additional insulin substitution (OT-group). In order to assess MYCL and intrahepatic lipid (IHLC) content as well as cardiac geometry and function magnetic resonance spectroscopy (MRS) and imaging (MRI) examinations were performed at baseline (IT and OT) and 10 days after initiation of IT. Follow up measurements took place 181±49 days after IT. Results Interestingly, basal MYCLs were 50% lower in IT- compared to OT-group (0.41±0.12 vs. 0.80±0.11% of water signal; p = 0.034). After 10 days of IT, an acute 80%-rise in MYCL (p = 0.008) was observed, while IHLC did not change. Likewise, myocardial mass (+13%; p = 0.004), wall thickness in end-diastole (+13%; p = 0.030) and concentricity, an index of cardiac remodeling, increased (+28%; p = 0.026). In the long-term MYCL returned to baseline, while IHCL significantly decreased (−31%; p = 0.000). No acute changes in systolic left ventricular function were observed. Conclusions/Interpretation The initiation of IT in patients with T2DM was followed by an acute rise in MYCL concentration and myocardial mass.